Occurrence of Hemotropic Mycoplasmas in Commercial Pig Herds in Southeastern Brazil - Daniele Soares Fialho; Agostinho Sérgio Scofano; Karyne dos Santos Marins da Silva; Katielle Ribeiro da Silva; Lara Celeste Araujo do Carmo Cordeiro; Nathalie Costa da Cunha; Elmiro Rosendo do Nascimento; Thomas Salles Dias (Microorganisms, 2025)
Mycoplasma suis infects pig red blood cells and is linked to anemia, weakened immunity, and production losses. Infected animals may remain subclinical carriers, contributing to pathogen dissemination. This study aimed to investigate the prevalence of M. suis in commercial pig farms in the state of Espírito Santo, Brazil. A total of 416 blood samples from 55 farms were analyzed using conventional PCR targeting the hemotropic Mycoplasmas (16S rRNA) and a species-specific PCR for M. suis (23S rRNA). Among the samples, 131 (31.49%) tested positive for hemoplasmas and 58 (13.94%) for M. suis with a significantly higher frequency in sows (p < 0.01). The Metropolitan microregion showed the highest prevalence (23.53%). The discrepancy between the prevalence for the genus and the species suggests the possible presence of other hemotropic Mycoplasma species and highlights the limitations of 16S rRNA-based assays. These findings emphasize the need for more specific molecular targets and continuous monitoring strategies to control infection in pig farming.